Handbook of research on global fashion management and merchandising - Vecchi, Alessandra; Buckley, Chitra 1959- (Hershey, PA Business Science Reference, 2016)
"This book explores the various facets of effective management procedures within the fashion industry, featuring research on entrepreneurship, operations management, marketing, business modeling, and fashion technology"-- Provided by publisher.
Preface -- Introduction -- Creativity and innovation -- Visionary leadership : learning from exemplary organizations -- Organizational leadership and resources in driving creativity and innovation -- The blending of luxury fashion brands and contemporary art a global strategy for value creation -- Strategic fashion management -- Strategic fashion management : influential factors in strategy implementation -- Entrepreneurial or not? : asymmetrical business models in UK fashion micro-enterprises -- Trade policy and its implications for sourcing fashion goods -- The luxury market in the fashion industry : a conceptual segmentation -- Fast fashion business model : an overview -- The implementation of fashion technology -- Fashion blog's engagement in the customer decision making process -- Fashion-technology & change in product development and consumption for the high-end menswear sector : a study utilizing a 3d-4C's process model -- How to use sizing technology and fashion metadata to improve the user experience for online fashion retail -- Augmented reality as a tool to enhance the experiential value of online shopping : the future of fashion retailing -- Techcouturism, an alternative showcase for new fashion designers -- Fusion of artisan and virtual : fashion's new world opportunities -- Fashion retail and its more recent dynamics -- Store openings and sourcing strategies in the internationalization of fashion industrial retailers -- Omnichannel fashion retail and channel integration the case of department stores : the case of department stores -- Multi-sensory fashion retail experiences : the impact of sound, smell, sight and touch on consumer based brand equity -- Brand experiences, retail scenarios, and brand images in the fashion industry -- CSR & sustainability -- Slow fashion and sustainability : the luxury impact -- The myth of sustainability in fashion supply chains -- CRM in fashion retai l: building store loyalty through store trust -- The challenge of sustainability within the Italian fashion system -- Fashion brand management : fashioning value through CSR -- International evidence -- The impact of e-commerce on the clothing retailers : studies on Chinese companies -- The role of cross-country differences in international fashion retailing : e-commerce development in Spain and the UK -- Fashion and social media : some illustrative evidence from Italian luxury brands -- The Russian luxury fashion goods market : development and perspectives -- Supplying what? : an analysis of the fashion apparel production in Brazil -- Benetton's response to the increasing global competition.
Includes bibliographical references (pages 738-846) and index.
Electronic reproduction.
Keywords: Fashion merchandising; Business logistics; Branding (Marketing); Electronic books